To solve the equation \( 5x - 12 - 6x = -10x + 7 - 1 \), let's follow the steps to fill in the blanks:
-
Combine like terms on both sides. \[ 5x - 6x - 12 = -10x + 7 - 1 \] Which simplifies to: \[ -x - 12 = -10x + 6 \]
-
Add \(10x\) to both sides to eliminate \(x\) from the right side. \[ -x + 10x - 12 = -10x + 10x + 6 \] Simplifying gives: \[ 9x - 12 = 6 \]
-
Add 12 to both sides to isolate the term with \(x\). \[ 9x - 12 + 12 = 6 + 12 \] This results in: \[ 9x = 18 \]
-
Divide both sides by 9 to solve for \(x\). \[ x = \frac{18}{9} \] Thus: \[ x = 2 \]
Putting it all together, the completed steps are:
- \( -x - 12 = -10x + 6 \)
- \( -x + 10x - 12 = 6 \)
- \( 9x - 12 + 12 = 6 + 12 \)
- \( x = \frac{18}{9} \)
Finally, we find that \( x = 2 \).